The representation of women in the family in Spanish television fiction - Lacalle, Charo; Gómez, Beatriz (Communication & Society-Spain, 2017)
The rise of television drama in the late nineties challenged comedy as the most popular and resilient genre of fiction. The diversity of themes and growing complexity of new narratives have relegated family representations - key to comedy's success-to contextualize sentimental and sexual relationships and, to a lesser extent, the work sphere of female characters. This article analyses the context and family relations of 709 female characters represented, with varying degrees of importance, in 84 programs of Spanish television fiction (series, serials, TV movies, miniseries and sketches) premiered in 2012 and 2013. The approach combines quantitative (SPSS coding) and qualitative (socio-semiotics and script theory) methods. The analysis reveals that Spanish television fiction offers a complex picture of family relationships, which mixes cliches and stereotypes, while trying to capture reality. Generational conflicts are the most common misunderstandings in everyday representations of female characters, although most of the women generally have the support of their families to address problems and difficulties of their exciting fictional experiences.
Keywords: fiction; television; family; woman; Spain; analysis; Emerging; Scopus